The Effect Of Financial And Non-Financial Compensation On Employee's Performance Of Hakasima Media Tv Of Bengkulu City - Ari Nurjama; Karona Cahya Susena; Lydia Gustina Putri (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This research aims to test whether there is an influence of Financial and Non-Financial Compensation on the Performance of Employees of Hakasima Media TV in Bengkulu City. Based on the characteristics of the research, 39 samples were obtained using the Census or Saturated sampling method. Based on the results of the Multiple Linear Regression research, it shows that Y=12,305+0.413+0.86 9+e which proves that Financial Compensation has a positive effect on the Employees’ Performance of Hakasima Media TV of Bengkulu City of 0.413, and Non-Financial Compensation has a positive effect on the Employees’ Performance of Hakasima Media TV of Bengkulu City of 0.869. The results of the t test show that Financial Compensation has t count> t table (3.455 > 2.028) and a significant value of 0.001 < 0.05, therefore Ho is rejected, which means that Financial Compensation has a positive and significant effect on the the employees’ performance of Hakasima Media TV of Bengkulu City, and Nonfinancial Compensation is quite dominant with t count > t table (10.642 > 2.028), and has a significance level of 0.000 < 0.05 then Ho is rejected which means that non-financial compensation has a significant and significant impact on the Employees’ Performance of Hakasima Media TV of Bengkulu City. Based on the F test (simultaneous) it is known that the significance value is 0.000 < 0.05 and calculated F> F table (89.769 > 3.26) which means that financial compensation and non-financial compensation have a significant effect on the Employees’ Performance of Hakasima Media TV of Bengkulu City. Based on the results of the determination coefficient test, it is known that Financial Compensation and Non-Financial Compensation have an effect on the Employees’ Performance of Hakasima Media TV of Bengkulu City of 0.833 or 83.3% and the remainder (100-83.3% = 16.7%) is influenced by other variables not examined in this research.